THE EFFECT OF LIFESTYLE ON SKIN AGING - Sandewa, Ele; Vitayani, Sri; Namirah, Hanna Aulia; Waspodo, Nurelly Noro; Safei, Imran (UNG, 2026)
Skin aging is a natural process influenced by intrinsic and extrinsic factors, with lifestyle-related exposures such as ultraviolet radiation, pollution, poor diet, smoking, alcohol consumption, and inadequate sleep contributing to its acceleration. However, research examining the comprehensive impact of lifestyle on objectively measured skin aging parameters in rural Indonesian populations remains limited. The novelty of this study lies in its focus on a rural community in Eastern Indonesia, combining a validated lifestyle assessment with objective clinical skin analysis to generate context-specific evidence. This study aimed to determine the influence of lifestyle on skin aging among individuals aged 30–40 years in Lipulalongo Village, Banggai Laut Regency, Central Sulawesi. An observational analytic study with a cross-sectional design was conducted on 60 respondents selected through simple random sampling. Lifestyle was assessed using the Lifestyle Assessment Questionnaire 2025, while skin aging was measured using the Vision Skin Analyzer based on hydration, elasticity, wrinkles, and pigmentation parameters. Data were analyzed using univariate and bivariate methods, with the Spearman rank correlation test applied due to the ordinal nature of lifestyle data. The results showed that most respondents had lifestyles requiring improvement (61.7%) or were at high risk (38.3%), with skin conditions predominantly classified as normal (28.3%) and slightly moist (21.7%). A significant moderate correlation was found between lifestyle and skin aging (P-value 0.001; r = 0.514). In conclusion, lifestyle significantly influences skin aging, highlighting the importance of targeted health education to promote healthier behaviors in similar rural populations